A Review: The Transformation Of The Meaning Of Kebaya From National Clothing To A Media Of Self-Representation And Lifestyle - Putu Diah Ari Kusumadewi; Mohammad Adam Jerusalem (Mudra Jurnal Seni Budaya, 2023)
As a cultural product of the Indonesians, Kebaya has become a national dress that sticks with its philosophical principles and values. However, along with the times and the influence of popular culture, the kebaya changed its design lines. It caused a transformation of the meaning of the Indonesian national dress into a medium of self-representation and the lifestyle of modern women. This review aims to analyze the transformation of the meaning of kebaya as a medium of self-representation and lifestyle. The method used is a narrative review by analyzing several articles using the PRISMA method. The analysis results show that the kebaya, as Indonesia's national dress, has design characteristics, materials, and accessories that contain philosophical meanings that reflect the personality of Indonesian women. The design transformation of the traditional kebaya gave birth to a modern kebaya far from the standard of the conventional kebaya. Modern kebaya is interpreted as a symbol representing the wearer's self-image and social class. The modern kebaya, as a medium of self-image and social class, gives birth to a new lifestyle in society, namely a consumptive lifestyle, because someone will carry out consumption activities continuously without considering the use value of the item. Besides being able to complete references related to kebaya, the results of this review are also expected to be input for related parties to maintain the traditional kebaya standard and consider ethics in buying kebaya so as not to create a consumptive lifestyle.